Field and model tests of riprap on steep slopes exposed to overtopping. Issue 2 (3rd April 2019) - Hiller, Priska H.; Lia, Leif; Aberle, Jochen
Abstract : The comparability of large-scale field tests of dumped and placed riprap with a stone diameter of 0.37 m and corresponding model tests in a scale of 1:6.5 was investigated in terms of stability, packing density and visually observed flow pattern. The tested riprap protections were exposed to overtopping on a slope of 1:1.5 (vertical: horizontal). The results for dumped riprap revealed similarity between the field and model tests based on the critical stone-related Froude number as a measure of the stability, packing density, flow pattern and overtopping depth. The field and model tests with placed riprap showed good agreement in regard to flow pattern and overtopping depth. However, the placed riprap in the model tests was denser packed and more stable than in the field indicating laboratory effects. Placed riprap withstood up to 10 times higher unit discharges than dumped riprap, 6–8 m 2 s −1 in the field tests.